Postmaster and other stories - Rabindranath Tagore (Kerala Insight Publica, 2023)
The short stories collected here were written between 1891 and 1917 by the Bengali poet, writer, painter, musician and mystic, Sir Rabindranath Tagore (1861-1941). Throughout these stories, Tagore's main interest is people and the kaleidoscope of human emotions, as men and women struggle with the restric- tions and prohibitions of contemporary Hindu society
Keywords: Short Stories; The Cabuliwallah; The Home Coming; Once There was a King; The Childs Return; Master Mashai; Subha; The Castaway; The Son of Rashmani; The Babus of Nayanjore